IMPLEMENTASI MODEL PEMBELAJARAN INOVATIF DALAM MATA PELAJARAN P5 UNTUK MENINGKATKAN HASIL BELAJAR SISWA DI SD NEGERI 79 KOTA BENGKULU - Asvio, Nova; Triyani, Triyani; marlini, Sili; Febiola, Niken; Adel, Adel (FAKULTAS TARBIYAH UNIVERSITAS QOMARUDDIN GRESIK - JAWA TIMUR, 2025)
This research aims to analyze the implementation of the Strengthening Pancasila Student Profile (P5) Project at SD Negeri 79 Bengkulu City and identify factors that support and hinder its success. P5 is part of the Independent Curriculum which emphasizes project-based learning to build 21st century character and skills in students. The research method used is a descriptive qualitative approach with data collection techniques through observation, interviews and documentation. The research results show that the application of the project-based learning model in P5 increases students' active participation, understanding of concepts, as well as critical and collaborative thinking skills. Students become more motivated in learning, more active in discussions, and more independent in completing assignments. In addition, the results of academic evaluations show an increase in understanding of concepts by 20% compared to before implementing this model. However, there are several obstacles in implementing P5, such as limited time, teacher readiness in designing projects, and limited facility support. By understanding the factors that influence the success of this program, it is hoped that this research can provide recommendations for educators and policy makers to optimize the implementation of P5 in elementary schools. This innovative learning model has the potential to be a solution in increasing the effectiveness of character-based education in Indonesia.